Manajemen Supervisi Sebagai upaya Peningkatan Mutu Pendidikan di SMAN 1 Panyabungan - Febri Yanti Damayanti Nasution; Laila Nur Sahwa; Nasli Agusti Sikumbang; Rizki Amanda; Kasman (CV. Alim's Publishing, 2026)
This study aims to describe the implementation of supervision management as an effort to improve the quality of education at SMAN 1 Panyabungan. Supervision is one of the functions of education management that plays an important role in improving the quality of the learning process, teacher competence, and the effectiveness of school management. This study uses a qualitative approach with a descriptive method. Data was obtained through observation, interviews, and documentation involving school principals, teachers, and education staff. The results of the study show that supervision management at SMAN 1 Panyabungan is carried out through the stages of planning, implementation, evaluation, and follow-up in a structured manner. The planning stage is carried out by preparing a supervision program according to the needs of the school, implementation is carried out through monitoring and teacher coaching activities, evaluation is carried out by assessing the results of supervision, while the follow-up is in the form of continuous improvement and development. Supervision activities have been proven to have a positive impact on improving teacher professionalism, learning quality, and achieving educational goals in schools. These findings confirm that effective supervision management can be one of the important strategies in improving the quality of education in a sustainable manner, while strengthening the role of school principals as quality improvement-oriented educational leaders.